Kebijakan Penanggulangan Stunting Di Indonesia - Erika Nur Khasanah; Dini Gandini Purbaningrum; Citra Andita; Dwi Ayu Setiani (Jurnal Akuntan Publik, 2023)
Indonesia is a country with a stunting prevalence that can still be categorized as high with a prevalence rate of 24.4%. Various efforts have been made by the government to be able to overcome the stunting problem that occurs through various policies and regulations as well as through national strategies and interventions. This paper aims to explain the national policies and regulations and strategies used on tackling stunting in Indonesia. The method used in this research is a literature study method where the technique is through library data collection, reading and taking notes, and managing research materials. Indonesia already has a number of national policies and strategies on stunting that are realized in the form of interventions both specific and sensitive. Specific interventions are carried out by the Health sector by focusing on priority goals and important goals, while sensitive interventions are carried out by sectors outside Health where they are carried out to increase access to nutritious food; increase awareness, commitment, and nutrition parenting practices of mothers and children; improve access and quality of nutritional and health services; and improve the provision of clean water and sanitation facilities. Policies and regulations that exist at the central level, must also be followed by follow-up in the regions to the village level and involve not only the health sector but also other related sectors.